Larviposition site selection mediated by volatile semiochemicals in Glossina palpalis gambiensis. (16th October 2020) - Geoffrey, Gimonneau; Ouedraogo, Romaric; Ernest, Salou; Jean‐Baptiste, Rayaisse; Buatois, Bruno; Solano, Philippe; Dormont, Laurent; Roux, Olivier; Bouyer, Jérémy
Abstract : 1. Tsetse flies ( Diptera: Glossinidae ) are K‐strategist species and deposit a single larva at 10‐day intervals in specific sites. As larviposition site selection strongly impacts reproductive success, the selection of larviposition sites is unlikely to be random and will be subject to strong selective processes, probably mediated by specific cues. 2. This study was designed to assess the existence of an aggregation effect in the palpalis group and to test its potential chemical nature (contact or volatile compounds). The larviposition site selection of Glossina palpalis gambiensis was studied according to the presence of conspecific and heterospecific larvae (morsitans group) buried in substrates. Three sets of experiments were performed with either individual or grouped gravid females and with or without physical access to the substrate. 3. In individual larviposition experiments, females were more likely to select trays with buried larvae than unconditioned sand (63.2% and 36.8%, respectively; P < 0.05). In the grouped experiment with substrate contact, females were more likely to larviposit in trays with conspecific (40%) or heterospecific (33%) buried larvae than in unconditioned sand (22%) or empty trays (5%; P < 0.05). The results were similar without substrate contact, but more pupae were deposited in empty trays (19%). 4. These results provide the first evidence for larval aggregation in G. p. gambiensis and suggest that larviposition site selection is mediated by volatile semiochemicals of larval or pupal origin. However, this larval aggregation does not seem to be species specific and therefore offers new options for the behavioural manipulation of these vectors. Abstract : The choice of larviposition sites by tsetse flies is governed by several factors, one of them being larval semiochemicals, which may explain larval aggregation. In all larviposition experiments, females selected trays where larvae were previously introduced in the substrate (either conspecific or heterospecific), even in the absence of physical contact with the substrate ( P < 0.05). These results provide the first evidence for larval aggregation in G. p. gambiensis and suggest that larviposition site selection is mediated by volatile semiochemicals of larval or pupal origin.